A non-conducting role of the Cav1.4 Ca2+ channel drives homeostatic plasticity at the cone photoreceptor synapse - J Wesley Maddox; Gregory J Ordemann; Juan AM de la Rosa Vázquez; Angie Huang; Christof Gault; Serena R Wisner; Kate Randall; Daiki Futagi; Nihal A Salem; Dayne Mayfield; Boris V Zemelman; Steven DeVries; et al. (eLife, 2024)
In congenital stationary night blindness, type 2 (CSNB2)—a disorder involving the Cav1.4 (L-type) Ca2+ channel—visual impairment is mild considering that Cav1.4 mediates synaptic release from rod and cone photoreceptors. Here, we addressed this conundrum using a Cav1.4 knockout (KO) mouse and a knock-in (G369i KI) mouse expressing a non-conducting Cav1.4. Surprisingly, Cav3 (T-type) Ca2+ currents were detected in cones of G369i KI mice and Cav1.4 KO mice but not in cones of wild-type mouse, ground squirrels, and macaque retina. Whereas Cav1.4 KO mice are blind, G369i KI mice exhibit normal photopic (i.e. cone-mediated) visual behavior. Cone synapses, which fail to form in Cav1.4 KO mice, are present, albeit enlarged, and with some errors in postsynaptic wiring in G369i KI mice. While Cav1.4 KO mice lack evidence of cone synaptic responses, electrophysiological recordings in G369i KI mice revealed nominal transmission from cones to horizontal cells and bipolar cells. In CSNB2, we propose that Cav3 channels maintain cone synaptic output provided that the nonconducting role of Cav1.4 in cone synaptogenesis remains intact. Our findings reveal an unexpected form of homeostatic plasticity that relies on a non-canonical role of an ion channel.